2017
DOI: 10.1002/cne.24273
|View full text |Cite
|
Sign up to set email alerts
|

Monosynaptic retrograde tracing of neurons expressing the G‐protein coupled receptor Gpr151 in the mouse brain

Abstract: GPR151 is a G‐protein coupled receptor for which the endogenous ligand remains unknown. In the nervous system of vertebrates, its expression is enriched in specific diencephalic structures, where the highest levels are observed in the habenular area. The habenula has been implicated in a range of different functions including behavioral flexibility, decision making, inhibitory control, and pain processing, which makes it a promising target for treating psychiatric and neurological disease. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…39 Furthermore, functional characterization of neuronal Gpr151 suggested that the gene is important in the paraventricular nucleus and could therefore be potentially implicated in food and drug seeking behaviors. 40 Future studies should therefore aim at delineating the potential role of serotonin, glucocorticoids and these two orphan GPCRs with regards to metabolic dysfunction observed in HD, in relation to modifying age of onset of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, functional characterization of neuronal Gpr151 suggested that the gene is important in the paraventricular nucleus and could therefore be potentially implicated in food and drug seeking behaviors. 40 Future studies should therefore aim at delineating the potential role of serotonin, glucocorticoids and these two orphan GPCRs with regards to metabolic dysfunction observed in HD, in relation to modifying age of onset of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in the NCBI database, the number of experimentally identified protein sequences is in great excess of that of experimentally determined protein structures inside the almost-half-a-century old PDB [1]. For instance, GPR151 is an proton-sensing G-protein coupled receptor (GPCR) originally identified as homologous to galanin receptors [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Motivationmentioning
confidence: 99%
“…A particular problem is the fact that even for Hb, which connections are well described for rats, there is still no complete scheme of afferent connections for mice described in the literature, despite a number of qualitative studies already done (Qin C, Luo M, 2009;Broms J et al, 2017). In other words, there is some (very low) probability that mice's MHb can be associated with LPA, and mice's LHb with TS and SFi.…”
Section: -The Problem Of Alternative Control Casesmentioning
confidence: 99%
“…The best way to investigate DiI injection for accuracy, it to test already known brain structures, whose connections are well described, for example, on Habenula (Hb). Hb is a paired structure of the intermediate brain, its afferent connections are described in detail in the literature both for rats (Herkenham M, Nauta WJ, 1977) and partially for mice (Qin C, Luo M. 2009;Broms J et al, 2017). It is known that Medial Habenular nuclei (MHb) is innervated by Septum nuclei, such as Triangular septal nuclei (TS) and Septofimbrial septal nuclei (SFi); Lateral Habenular nuclei is innervated by the Lateral pteoptic area (LPA).…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation